A comparative analysis of dynamic management in marine and terrestrial systems. Issue 9 (27th July 2020) - Oestreich, William K; Chapman, Melissa S; Crowder, Larry B
Abstract : Protection of highly mobile species and shifting habitats is a practical challenge for conservation in both marine and terrestrial systems, particularly in light of the acceleration of land‐use change and climate‐driven range shifts. Static protected areas have long been a keystone of conservation but are generally insufficient for such species and habitats. Spatially and temporally dynamic management (DM) has arisen as a potential solution to this challenge. We present what we believe to be the first comparative analysis of DM across marine and terrestrial systems, focusing on the scales of DM approaches. Our results show that marine DM has largely been focused on relatively finer temporal scales, whereas terrestrial DM has focused on relatively finer spatial scales, often following the scale of available and relevant datasets. We explore not only the constraints imposed by data availability but also other drivers of DM trends and scales, highlighting areas in which exchange of approaches pioneered in each domain may be beneficial.